An Analysis of Commissive Speech Act in Film - Baihaqi, Yasmika; Widyantari, Wuri; Refai, Refai (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Speech Acts are utterances spoken by people to make a statement or describe something that affects the future. Examples are promises, threats, refusals, offers, warnings. This study aims to examine the use of Commissive Speech Acts in the film